2015
DOI: 10.1039/c4ja00264d
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet radiation combined with microwave-assisted wet digestion of Antarctic seaweeds for further determination of toxic elements by ICP-MS

Abstract: In this work, the use of ultraviolet radiation combined with microwave-assisted wet digestion (MW-UV) was applied for digestion of seaweed samples and further determination of As, Cd and Pb by inductively coupled plasma mass spectrometry (ICP-MS). In the proposed method, UV radiation was generated in situ by electrodeless Cd discharge lamps inserted into digestion quartz vessels. This approach increased the digestion efficiency allowing lower consumption of acids. The feasibility of using diluted acid solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…However, one drawback of UV-photolysis is the long irradiation time of 1–24 ​h ( De Borba et al., 2014 ). But UV-photolysis in combination with MW reduces the digestion time to half an hour for many matrices ( Pereira, Wiltsche, Knapp, Flores ; Hartwig et al., 2017 ; Hartwig et al., 2016 ; Cerveira et al., 2020 ; Dash et al., 2012 , 2016 ; Iop et al., 2017 ; Mesko et al., 2015 ). This formed the basis of using microwave assisted UV digestion of cereal flours in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…However, one drawback of UV-photolysis is the long irradiation time of 1–24 ​h ( De Borba et al., 2014 ). But UV-photolysis in combination with MW reduces the digestion time to half an hour for many matrices ( Pereira, Wiltsche, Knapp, Flores ; Hartwig et al., 2017 ; Hartwig et al., 2016 ; Cerveira et al., 2020 ; Dash et al., 2012 , 2016 ; Iop et al., 2017 ; Mesko et al., 2015 ). This formed the basis of using microwave assisted UV digestion of cereal flours in our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the growing interests toward the implementation of ''Green Chemistry'' principles, recent studies indicated that the use of dilute mineral acids along with auxiliary reagents such as H 2 O 2 for the quantitative extraction of a wide range of elements in various solid matrices can be achieved [47][48][49]. The two major components with a high influence on the MWD procedure are the concentration of nitric acid and auxiliary reagent H 2 O 2 [47,48].…”
Section: Optimization Of Acid Composition For Microwave-assisted Totamentioning
confidence: 99%
“…The use of diluted solutions is an important feature because high acid concentration of digests can cause interferences in ICP-based analytical techniques [18]. In this way, microwave-assisted ultraviolet digestion (MW-UV) has been applied to reduce the organic carbon from natural water [19] and for digestion of skimmed milk [20], Antarctic seaweeds [21] and crude oil samples [17] using diluted acids. This method is based on the use of an electrodeless discharge lamp, which is activated by microwave radiation in a closed system that enables an efficient digestion at high temperature and pressure [17,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, microwave-assisted ultraviolet digestion (MW-UV) has been applied to reduce the organic carbon from natural water [19] and for digestion of skimmed milk [20], Antarctic seaweeds [21] and crude oil samples [17] using diluted acids. This method is based on the use of an electrodeless discharge lamp, which is activated by microwave radiation in a closed system that enables an efficient digestion at high temperature and pressure [17,[19][20][21]. Despite the advantages of the combination of microwaves with ultraviolet radiation (e.g., use of diluted reagents, high efficiency of organic matter digestion, compatibility of digests with atomic spectrometric techniques, etc.)…”
Section: Introductionmentioning
confidence: 99%